Readability Level of Mathematics Textbook for Sixth Grade in Jordan - Aljabali , Laila (Dirasat: Educational Sciences, 2020)
The study aims at measuring the level of the readability of mathematics textbooks for sixth grade students in Jordan. To achieve the goals of the study, a cloze test was designed for five texts of the textbook selected from the Unit of Statistics and Probability. The sample of the study consisted of (800) male and female students who were selected randomly from the population; the number of male students was (400) and the number of female students was (400). The findings of the study revealed that (%22.5) of the study sample was at the level of frustrating type (%33.8) of education type, and (%438) of independent type. The findings also revealed that there are statistically significant differences in the readability level between males and females in favor of females. The study recommended utilizing a cloze test before publishing mathematics textbooks to ensure its suitability for students.